Models of Financing in Education - Sonny Muhammad Ikhsan Mangkuwinata; Aswita Nova; Buchari; Fitrie Rahmawaty; Suriyani (Journal Informatic, Education and Management (JIEM), 2025)
Educational financing is a vital component of the education system that plays a significant role in ensuring equitable access, improving quality, and enhancing the efficiency of educational implementation. This study examines various education financing models implemented in Indonesia, ranging from government and community-based sources to philanthropic and social solidarity alternatives such as ta’awun funds. The purpose of this article is to explore and analyze the models of education financing. The method used is a literature review by collecting information from various sources relevant to the topic. The results indicate that Indonesia applies a mixed financing system, which is a modification of several international models, such as the Power Equalizing model, the Foundation Plan, and direct subsidy schemes like the School Operational Assistance (BOS). Previous studies emphasize the importance of careful planning, strong supervision, and accountability in managing education funds. Furthermore, the decentralization of education requires synergy between the central and local governments to ensure effective budget utilization. In conclusion, no single model is entirely ideal; therefore, a combination of models that are adaptive to the socio-economic conditions of each region, while considering the principles of equity, efficiency, and sustainability, is necessary. With effective financing, education in Indonesia is expected to become a key driver of human resource development and national progress.